2018
DOI: 10.2147/cmar.s163747
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NSAIDs activity in COX-2 expressing and non-expressing 2D and 3D pancreatic cancer cell cultures

Abstract: PurposeIn this study, we evaluated the anticancer activity of non-steroidal anti-inflammatory drugs (NSAIDs) in BxPC-3 and MIA PaCa-2 pancreatic cancer cell cultures.MethodsTo test the effect of compounds on the viability of cells, the MTT assay was used. The activity of NSAIDs in 3D cell cultures was evaluated by measuring the size change of spheroids. The type of cell death was identified by cell staining with Hoechst 33342 and propidium iodide. To evaluate the effect on the colony-forming ability of cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It was observed that consumption of NSAIDs can lead to high incidence of gastrointestinal irritation due to the development of life-threatening gastrointestinal ulcers and also causes abnormal renal physiology. COX-2 is overexpressed in numerous premalignant and malignant lesions con rmed the signi cant correlation between the COX-2 inhibition activity of non steroidal anti-in ammatory drugs (NSAIDs) and their antitumor e cacies (Ceponyte et al 2018). Thus, celecoxib (CXB), a selective COX-2 inhibitor, showed promising results in the prevention tumor cell growth and suppress tumor angiogenesis and metastasis Xu et al 2011).…”
Section: Discussionmentioning
confidence: 94%
“…It was observed that consumption of NSAIDs can lead to high incidence of gastrointestinal irritation due to the development of life-threatening gastrointestinal ulcers and also causes abnormal renal physiology. COX-2 is overexpressed in numerous premalignant and malignant lesions con rmed the signi cant correlation between the COX-2 inhibition activity of non steroidal anti-in ammatory drugs (NSAIDs) and their antitumor e cacies (Ceponyte et al 2018). Thus, celecoxib (CXB), a selective COX-2 inhibitor, showed promising results in the prevention tumor cell growth and suppress tumor angiogenesis and metastasis Xu et al 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Uncontrolled migration of cancer cells is the first step towards invasion and metastasis [48] . Since many NSAIDs do possess anti‐cancer activity [49] and our main goal of the present work is to develop supramolecular metallogels for drug delivery applications, we decided to evaluate anti‐cancer behaviour of the metallogelator complexes i. e. 3‐PyMEC , 3‐PyDIC , 4‐PyNAP and 4‐PyMEC on a highly aggressive human breast cancer cell line MDA‐MB‐231 by MTT assay (for detail, see experimental). MTT assay data revealed that 3‐PyMEC possessed the best anti‐cancer property against the cell line amongst the gelator complexes studied herein; nearly 96% cancer cell death was observed at a concentration of 35 μM of 3‐PyMEC (Figure S23).…”
Section: Resultsmentioning
confidence: 99%
“…The potential cytotoxic effect of Iris extracts on certain cell lines was determined by a MTT viability assay as described before [ 87 ]. Details can be found in the Supplementary Materials section .…”
Section: Methodsmentioning
confidence: 99%